A terpyridine-appended hexaarylbenzene fluorophore: synthesis, photophysical properties and application for the colorimetric detection of Fe2+ in aqueous solution. (2nd February 2023) - Tian, Xiaochang; Li, Jianye; Gu, Cancan; Yin, Guohui; Zhang, Yuecheng; Zhao, Jiquan; Cao, Xiaohui
Abstract : A hexaarylbenzene-based push–pull fluorophore featuring unusual uphill emission was prepared, which can act as a colorimetric sensor for detecting Fe 2+ . Abstract : The hexaarylbenzene (HAB)-based push–pull fluorophore HAB-MeO-TPy with the 2, 2′:6′, 2″-terpyridine (TPy) unit as an acceptor and the methoxy (MeO) group as a donor was developed. It was observed that HAB-MeO-TPy exhibited an unusual uphill-type emission with increasing solvent polarity from cyclohexane to DMSO. By comparison with a previously reported fluorophore HPB-MeO-DCV, a structure–property relationship regarding this uncommon fluorescence behavior was disclosed. Furthermore, the sensing properties of HAB-MeO-TPy for metal ions were also investigated. In the presence of Fe 2+, HAB-MeO-TPy displayed a visual color change from colorless to magenta, indicating that HAB-MeO-TPy can act as a "naked eye" sensor for Fe 2+ detection. From absorption titration experiments, the detection limit was determined to be 1.50 × 10 −7 M. In addition, HAB-MeO-TPy was successfully applied to detect Fe 2+ in real water samples.